Influence of training on Taiwanese elementary school English teachers' professional identity construction. Issue 4 (4th July 2019) - Chien, Chin-Wen
ABSTRACT: English teachers' professional identity construction is an on-going process of identification and negotiation of personal self-roles, prior experiences in learning and teaching, and the roles promoted by institutional and social practices. Based on the conceptual framework adopted from Wetzler's (2010) Key Drivers of Teacher Learning, documents, interviews, and observation notes were used to analyse 19 Taiwanese elementary school English teachers' professional identity construction during the series of training sessions. The study produced some major findings. First, participants' professional identities were viewed by different types of agency, constructed through situations, and fostered via different kinds of connections. Secondly the training sessions led English teachers to exercise their reflective practice.